2022
DOI: 10.1038/s41590-022-01165-7
|View full text |Cite|
|
Sign up to set email alerts
|

B lymphocyte-derived acetylcholine limits steady-state and emergency hematopoiesis

Abstract: Autonomic nerves control organ function through the sympathetic and parasympathetic branches, which have opposite effects. In the bone marrow, sympathetic (adrenergic) nerves promote hematopoiesis; however, how parasympathetic (cholinergic) signals modulate haematopoiesis is unclear. Here we show that B lymphocytes were an important source of acetylcholine, a neurotransmitter of the parasympathetic nervous system which reduced hematopoiesis. Single cell RNA sequencing identified 9 clusters of cells that expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…Previously, we have identified lung B cells as a significant source of non-neuronal ChAT and thus ACh synthesis in mice ( 4 ). Therefore, in line with previous studies ( 24 , 28 ), it is possible that B cell production of ACh regulates neutrophil trafficking at homeostasis in the lung.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we have identified lung B cells as a significant source of non-neuronal ChAT and thus ACh synthesis in mice ( 4 ). Therefore, in line with previous studies ( 24 , 28 ), it is possible that B cell production of ACh regulates neutrophil trafficking at homeostasis in the lung.…”
Section: Discussionsupporting
confidence: 85%
“…Both are involved in the sleep-wake cycle, but serotonergic pathways control a variety of other processes, including emotional behavior, circadian rhythm, appetite, and many visceral activities such as sexual behavior, and gastrointestinal movements ( 35 ). Likewise, the parasympathetic neurotransmitter acetylcholine was found to be produced by B lymphocytes and to negatively regulate hematopoiesis ( 36 ), by T lymphocytes and to control viral infection ( 37 ), and by type-2 Innate Lymphoid Cells (ILC2) and to promote anti-helminth immunity ( 38 ) ( 39 ).…”
Section: The Immune System Like the Nervous Systemmentioning
confidence: 99%
“…Using various approaches, including multiple reporter mouse lines such as ChAT-eGFP mice, which express enhanced green fluorescence protein (eGFP) under the control of the choline acetyltransferase promoter (Chat, the rate-limiting enzyme for ACh biosynthesis), many studies have now convincingly shown that non-neuronal cells, including various types of immune cells, can synthesize ACh [40,41,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Functionally, murine T cells expressing ChAT can inhibit cytokine release [67].…”
Section: Cholinergic Machinery In Immune Cellsmentioning
confidence: 99%
“…ChAT-expressing B cells have been reported to diminish the recruitment of neutrophils in mice, thus regulating local innate immunity [70]. Specifically, ACh released from ChAT + B cells in bone marrow curbs myelopoiesis, and, in mice harboring B cell-specific Chat deletion, increased accumulation of inflammatory myeloid cells has been reported to worsen symptoms of myocardial infarction [80]. Moreover, ChAT expression has been observed in murine macrophages in several studies [70,78]; however, aside from ChAMs being able to regulate beige fat, the physiological function of ChAT in macrophages has not been elucidated.…”
Section: Cholinergic Machinery In Immune Cellsmentioning
confidence: 99%